Dyslipidemia in Children with Arterial Ischemic Stroke: Prevalence and Risk Factors - Sultan, Sally (Pediatr Neurol, 2017)
BACKGROUND: Risk factors for pediatric stroke are poorly understood and require study to improve prevention. Total cholesterol (TC) and triglyceride (TG) values peak to near-adult levels before puberty, a period of increased stroke incidence. The role of lipids in childhood arterial ischemic stroke (AIS) has been minimally investigated. SUBJECTS/METHODS: We performed a cross-sectional analysis of lipid and Lp(a) concentrations in children with AIS in the International Pediatric Stroke Study (IPSS) to compare the prevalence of dyslipidemia and high or low ranking lipid values in our dataset to reported population values. We tested sex, BMI, race, ethnicity, family history and stroke risk factors for associations with dyslipidemia, high non-HDL-c and hypertriglyceridemia. RESULTS: Compared with the National Health and Nutrition Examination Survey, a higher proportion of children ≥5 years with AIS had dyslipidemia (38.4% vs 21%), high-TC (10.6% vs 7.4%), high non-HDL-c (23.1% vs 8.4%) and low-HDL-c (39.8% vs 13.4%). The lipid values that corresponded to one standard deviation above the mean (84.13(th)%tile) in multiple published national studies generally corresponded to a lower ranking percentile in children ≥5 years with AIS. Dyslipidemia was more likely associated with an underweight, overweight or obese BMI compared with a healthy weight. Ethnic background and an acute systemic illness were also associated with abnormal lipids. CONCLUSIONS: Dyslipidemia and hypertriglyceridemia may be more prevalent in children with arterial ischemic stroke compared with stroke-free children.